Evaluation Competencies and Evaluation Use: Some Reflections - Soma De Silva (The Evaluation Center at Western Michigan University, 2023)
This article aimed to identify the emphasis on evaluation use within evaluation competency frameworks. A review of evaluation competency frameworks shows an underlying focus on evaluation use in all frameworks. Nevertheless, specific competencies explicitly focusing on evaluation use were incorporated in more recent frameworks, reflecting the increasing attention to evaluation use. A theory of change for evaluation use is proposed depicting the role of competencies of evaluators and critical users. The article argues for more emphasis on directly use related competencies and extending the competencies beyond evaluators to users. It proposes establishing standardized and up-to-date evaluation training in academic institutions to professionalize evaluation and thereby promote the integration of evaluation in development interventions.   Keywords: competency frameworks, evaluation competencies, use of evaluation, evaluation training, development interventions.